2019
DOI: 10.1371/journal.pone.0226609
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamics of plasma micronutrient concentrations and their correlation with serum proteins and thyroid hormones in patients with paracoccidioidomycosis

Abstract: Minerals, such as zinc, copper, and iron are reported to play roles in chronic infectious diseases; however, their role in paracoccidioidomycosis (PCM) remains unknown. This study aimed to examine the micronutrient dynamics and their correlation with serum proteins and thyroid hormones in patients with PCM. In 14 patients with PCM and 10 healthy subjects, we evaluated the body mass index (BMI) along with serum levels of hemoglobin, iron, ferritin, zinc, copper, magnesium, albumin, globulin, thyroid stimulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Additionally, severe cases were associated with higher ferritin levels, probably because of the production of IL-6 caused by fungal infection. A previous study by our group reported similar results [14].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Additionally, severe cases were associated with higher ferritin levels, probably because of the production of IL-6 caused by fungal infection. A previous study by our group reported similar results [14].…”
Section: Discussionsupporting
confidence: 86%
“…The host-parasite interaction and consequent inflammatory response lead to changes in iron metabolism dynamics. These changes can be observed in some patients with PCM [14], which is a chronic systemic inflammatory disease requiring long-term treatment. Understanding the frequency and intensity of iron metabolism disturbances in patients with chronic PCM will help improve therapeutic management.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are more commonly reported in the acute/subacute form of the disease. Few studies on blood cells in chronic PCM have been described, showing changes in the number of erythrocytes and the concentration of hemoglobin [8], as well as in the subpopulations of monocytes and lymphocytes, in untreated patients [9][10][11]. The complete blood count is a simple test performed routinely in most clinics and is important in the clinical management of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies on blood cells in chronic PCM have been described, showing changes in the number of erythrocytes and the concentration of hemoglobin [14], as well as in the subpopulations of monocytes and lymphocytes, in untreated patients [15][16][17]. The complete blood count is a simple test performed routinely in most clinics and is important in the clinical management of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%